Urgensi Pendidikan Agama Islam Dalam Membentuk Karakter Anak Di Sekolah Dasar - Miftakhuddin, Miftakhuddin; Imron, Imron (Prosiding University Research Colloquium, 2021)
The phenomenon that shows that there is a lot of moral decline can result in the vulnerability of religious moral values to students. This can cause several negative impacts, including brawls between students, anarchic demonstrations, drug use, promiscuity, deviant behavior, and many other negative impacts. For this reason, a good moral or character formation is needed for children through Islamic religious learning in schools. Moral or moral is one of the main teachings of Islam that must be prioritized in Islamic education to be taught or instilled in students, with the intention of forming people with strong and good personalities (morals). This paper is a reminder for us that religious education has an important role in character building in elementary schools. We also gain knowledge about the method of implementing the learning process of Islamic religious education in the formation of the character of Abdurrahman an-Nahlawi’s perspective.